Purification and Characteristics of Sorbitol-6-phosphate Dehydrogenase from Loquat Leaves - Hirai, Masashi (1981)
To study the role of sorbitol-6-phosphate dehydrogenase in sorbitol synthesis in leaves of Rosaceous plants, properties of the enzyme and its presence in several plants in the family was investigated. The activity of the enzyme, which catalyzes an NADP-dependent oxidation of the substrate to glucose-6-phosphate, was detected in leaves of Prunus mume, Prunus persica, Rhaphiolepsis indica, Sorbus aucuparia, Cydonia oblonga, Photinia glabra, Sorbaria kirilowii, and Spiraea thunbergii. The enzyme was purified about 60-fold from leaves of loquat (Eriobotrya japonica) using affinity chromatography with Blue Sepharose. Neither mannitol-1-phosphate nor fructose-6-phosphate served as substrate. Molecular weight of the enzyme was calculated to be 65,000 at pH 8.0 by gel filtration. Since sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed a peptide of 33,000 daltons, the enzyme was assumed to be a dimer at pH 8.0 K(m) values for sorbitol-6-phosphate, glucose-6-phosphate, NADP, and NADPH were 2.22 millimolar, 11.6 millimolar, 13.5 micromolar, and 1.61 micromolar, respectively. Equilibrium constant for sorbitol-6-phosphate oxidation was 5.12 × 10(−10). Optimal pH for sorbitol-6-phosphate oxidation was 9.8. The enzyme showed its maximum activity within a broad pH range between 7 and 9 for glucose-6-phosphate reduction. The enzyme was more effective in the direction of glucose-6-phosphate reduction than in the reverse direction at neutral pH. Thus, it is suggested that the enzyme catalyzes sorbitol synthesis from glucose-6-phosphate during photosynthesis in leaves of Rosaceous plants.